Seal Impressions on the 1689 and 1860 Sino-Russian Treaties: Material Culture in Diplomatic Culture - Chia Ning (Athens Journal of History)
This study underscores the crucial role of seal impressions on Sino-Russian treaties, viewing the indifference of seal-created visual information as a significant defect in current treaty scholarship. This research proposes that the analysis of material seals holds equal importance to the textual examination of written articles in comprehending SinoRussian diplomatic culture. The mandatory use of official seals for signing bilateral treaties in both the Qing and Russian Empires is deeply rooted in their unique civilizations and traditions. From this background, the political culture of these empires guided the treaty negotiators to perceive the seal impressions on treaties not only as mutual commitments to fulfilling the treaty promises but also as a non-linguistic means to engage with their respective relationship positions. As a result, both written articles and visual sigillography are invaluable as primary sources in treaty research.